THU0251 Familial clustering of autoimmune diseases in sjÖgren's syndrome: an italian case-control study. (1st June 2001) - Priori, R; Conti, F; Cassarà, E; Medda, E; Stazi, MA; Tomassini, C; Bozzolo, E; Franceschini, F; Urbano, T; Giacomelli, R; Valesini, G
Abstract : Background: Autoimmune diseases often cluster in families. Objectives: Aim of this study was to investigate the prevalence, the incidence and the risk for autoimmune diseases (AD) in first degree relatives (FDR) of italian Sjögren's syndrome (SS) patients. Methods: A multicentre case-control study was performed in Italy. Cases (patients classified as SS according to 1994 EEC criteria) and controls (subjects without known history of autoimmune disorder) were randomly selected and interviewed by a trained medical doctor. Data on family history of AD in FDR were recorded. We calculated the incidence rate of AD in the two groups by dividing the number of cases of AD by person-years (py) at risk. The relative risk (RR) was estimated by dividing the incidence rate among relatives of cases by the incidence rate among relatives of controls. Furthermore we conducted stratified analyses according to sex of relatives and/or proband to evaluate whether the relation between SS in FDR and AD differs by sex. Statistical analyses were performed using STATA software. Results: 143 SS cases and 140 controls were enrolled. 34/143 (23.8%) and 8/140 (5.7%) had at least one FDR with AD (p < 0.01); 44/839 (5.24%) FDR of SS patients and 12/776 (1.55%) FDR of controls had AD (p < 0.01). We estimated an incidence rate of 1.03 × 1000 py in SS group and 0.32 × 1000 py in control group. The ratio of incidence density showed that relatives of SS cases have three time probability to have an AD compared to relatives of controls (RR 3.24, CI 95% 1.71–6.14). We found that the risk for AD is epecially pronounced in relatives of female probands and it increases if the FDR is female, too. Conclusion: This case-control study confirms the clustering of AD in SS families and defines the risk to have an AD for first degree relatives of patients with SS.